GEV DISTRIBUTION AND PARAMETER ESTIMATION FOR VAN EARTHQUAKE DATA - Şehribanoğlu Sanem (Scientific Journal of Pedagogy and Economics, 2020)
Probabilistic extreme value theory is an interesting and fascinating theory with a great variety of applications. In probability theory and statistics, this distribution is used to model extreme (maximum or minimum) observations. Generalized Extreme Value (GEV)distribution is frequently applied to forecast natural events such as floods, air pollution, extreme sea levels, hydrology, meteorology, climatology, insurance, finance, geology and seismology. In this study general information about Maximum Likelihood Estimation and Bayesian Inference were investigated using the parameter estimation methods. The application of the study was completed using earthquake data from Van provincial center in Turkey from 1995 to 2017. This data used the Maximum Likelihood Estimation and Bayesian Estimation methods in an attempt to predict the severity of earthquakes expected to occur in the future